A SYSTEMS ENGINEERING APPROACH TO SUSTAINABILITY DECISION SUPPORT SYSTEM BASED ON HESI - Syaukani, Muhammad (Jurnal Rekayasa Perangkat Lunak dan Sistem Informasi, 2025)
Climate change and global sustainability demands are prompting universities to integrate sustainable principles into all academic and non-academic activities. This research led to the design and implementation of a Sustainability Decision Support System (SDSS) at Institut Teknologi Bisnis dan Bahasa Dian Cipta Cendikia (ITBA-DCC), using the System Engineering Process (SEP) and the Higher Education Sustainability Initiative (HESI) framework. The SDSS uses Multi-Criteria Decision Making (MCDM) and interactive data visualization to assess sustainability across four dimensions: environmental, social, economic, and governance. Initial pilot testing showed an overall sustainability index of 74/100, with the highest score in the environmental dimension (82/100) and the lowest in governance (68/100). User Acceptance Testing (UAT) reported a 91% satisfaction rate among staff, lecturers, and campus leaders. Although the system relies on annual data and some manual inputs, the SDSS shows potential for adoption by similar institutions and supports Sustainable Development Goals (SDGs) in higher education.